Transformasi Perpustakaan Sekolah: Strategi Pengelolaan Efektif di SD Negeri Sinar Palembang, Lampung Selatan - Piati, Alip; Mubarok, Alfian (Hadara : Journal of Da'wah and Islamic Civilization, 2025)
This study aims to analyze the transformation of the school library in improving literacy and the quality of education at SD Negeri Sinar Palembang, South Lampung. The transformation of the library plays a crucial role in fostering a culture of literacy, increasing students’ reading interest, and strengthening the library’s function as a learning center. This research employs a qualitative approach with a case study design, utilizing observation, interviews, and documentation techniques. The findings reveal that the transformation includes physical revitalization of the library, enhancement of librarian competencies, and the development of engaging literacy programs for students. Activities such as reading clubs, writing competitions, and storytelling sessions have proven effective in increasing student participation and fostering reading interest. However, challenges such as limited funding and technological facilities hinder the optimal management of the library. The transformation of the school library has succeeded in creating an active, creative, and enjoyable learning environment while reinforcing the culture of literacy in elementary education. The implications of this research are expected to serve as a reference for other schools in developing innovative and sustainable library management strategies.